ACT Family Violence Intervention Program review - Mathew Lyneham
This paper reports on a review of the Australian Capital Territory’s Family Violence Intervention Program, which provides an interagency response to family violence matters. The scope of the review was to analyse the program’s activities and outcomes using 2007–08 data provided by participating agencies, supported by in-depth interviews with key stakeholders including victims whose matters had been finalised in court. After the completion of this report, additional data from 2008–09 and 2009–10 was made available by some Family Violence Intervention Program (FVIP) participating agencies. Although not within the scope of this evaluation, these data pointed to some preliminary improvements in the FVIP